Optimalisasi Penerapan Etika Bisnis Syariah Berbasis Maqasid Syariah di Dapur Kue Rosad Gondang Mojokerto: Sebuah Analisis Strategis untuk Peningkatan Kualitas dan Keberlanjutan Usaha - Wiyono, Joko (FADZAT: Jurnal Ekonomi Syariah, 2022)
This study explores the implementation of Sharia business ethics and the principles of Maqasid Shariah within the operations of Dapur Kue Rosad Gondang Mojokerto, a culinary business in Indonesia. The primary aim of this research is to identify how the application of Sharia values can influence business sustainability and social welfare. Utilizing a qualitative approach, the study collected data through in-depth interviews, participatory observation, and analysis of company documents. The findings indicate that Dapur Kue Rosad has made significant initial steps in integrating Sharia business ethics, focusing on halal product compliance and fair transaction practices. However, the results also suggest that a broader application of Maqasid Shariah principles, aiming to protect religion, life, intellect, progeny, and wealth, requires enhancement, especially in aspects of environmental sustainability and social engagement. The study recommends the development of robust internal policies, enhancement of standardization and certification, staff training programs on Sharia ethics, and innovation in products and services that support social welfare as strategies to improve the implementation of Sharia business ethics and Maqasid Shariah principles. These findings provide valuable insights for culinary businesses and other Sharia-compliant enterprises in integrating Sharia values to achieve sustainable and socially responsible success. This research highlights the importance of adopting a holistic approach in applying Sharia business ethics, not just focusing on legal compliance but also on making a positive contribution to society and the environment.